Resource-Aware Contracts for Addressing Feature Interaction in Dynamic Adaptive Systems - MEIER, RENE (IEEE Computer Society Press, 2009)
Dynamic adaptive systems are becoming increasingly popular due to their ability to adapt to heterogeneous and changing environments. Such systems must avert adverse feature interaction where the adaptation of an existing feature or the introduction of a novel feature may result in unexpected and possibly adverse system behavior. This paper proposes resource-aware contracts for addressing adverse feature interaction in dynamically adaptable systems resulting from resource constraints. Resource-aware contracts explicitly capture the resource requirements of the individual components comprising a system. They are considered a fundamental means towards detecting and ultimately resolving adverse feature interaction and a key enabler of dynamic system adaptation.
the Fifth International Conference on Autonomic and Autonomous Systems (ICAS 2009)
PUBLISHED
Valencia, Spain
Keywords: Computer Science